The Maximum Complete (k,n)-Arcs in the Projective Plane PG(2,4) By Geometric Method - Kadhum, S. J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A (k,n)-arc A in a finite projective plane PG(2,q) over Galois field GF(q), q=pâ¿ for same prime number p and some integer nâ‰¥2, is a set of k points, no n+1 of which are collinear. A (k,n)-arc is complete if it is not contained in a(k+1,n)-arc. In this paper, the maximum complete (k,n)-arcs, n=2,3 in PG(2,4) can be constructed from the equation of the conic.